Medicare Austerity Reforms and Patient Out-of-Pocket Costs: The Experience from Australian Cancer Patients - Maryam Naghsh Nejad; Kees Van Gool; Philip Haywood; Jane Hall (Institute of Labor Economics (IZA), 2024)
In this paper, we examine trends in provider fees charged, government expenditure on private out-of-hospital medical services, and out of pocket costs following policy changes intended to reduce government expenditure. We examine the experience of a high-need patient group: people diagnosed with cancer. The Australian system for these services is predominantly publicly funded under fee for service; with no government control on the fees charged by providers. We calculate out of pocket costs for patients in the 12 months following on cancer diagnosis and find a large variation in these costs according to the type of treatment received as well as the place of residence and presence of additional government protection. We find that volumes of services, provider fees, and out of pocket costs rose over time. These findings are especially important for a high-need patient group as out of pocket costs are considered a barrier to access to health care. Governments may respond to the long-term fiscal challenges due to the COVID-19 pandemic by attempting to constrain benefits it pays; our results demonstrate that careful consideration of the full impact of such policies is needed.
Keywords: I13; I14; I11; 330; public health insurance; cancer; out of pocket costs